Part of the solution: A survey of community organisation perspectives on barriers and facilitating actions to Advance Care Planning in British Columbia, Canada. (14th December 2021) - Siden, Ellie G.; Carter, Rachel Z.; Barwich, Doris; Hassan, Eman
Abstract: Background: Despite the established benefits of Advance Care Planning (ACP), engagement remains low in British Columbia. Since 2016, a growing number of community‐based nonprofits have offered ACP education. To date, no study has focused on the perspectives of nonprofits on ACP in British Columbia. Objective: This study aimed to identify barriers and facilitating actions to ACP as perceived by British Columbian nonprofits. Design: A mixed‐methods design was used. Data were collected through online surveys and telephone interviews. Setting and Participants: Staff and volunteers from British Columbian nonprofits that are providing or interested in providing public education on ACP were recruited for this study. Results: The lack of public awareness of ACP, the emotional difficulty of the conversation, the complicated ACP process, the belief that ACP is synonymous with completing a medical order form, the challenge of introducing ACP in different cultural contexts and the siloed approach to ACP education were rated as the most important barriers to ACP engagement. The most important facilitating actions were developing clear messages, improving ACP literacy, reframing ACP as part of life planning, simplifying ACP documentation and transfer, integrating ACP conversations into clinical practice and better collaboration between the health system and nonprofits. Discussion: This study identifies numerous opportunities to improve ACP engagement in British Columbia from a community lens. To maximize ACP engagement, community‐led ACP education should be offered in coordination with the health system. Conclusion: Community‐led ACP education as well as collaboration and consultation with nonprofits are part of the solution to the low ACP engagement in British Columbia. Public Contribution: Study participants, including staff and volunteers at nonprofits, are members of the public.